Effects of alcohols and dissolved gases on sonochemical generation of hydrogen in a 300 kHz sonoreactor - Jongbok Choi; Seokho Yoon; Younggyu Son (Ultrasonics Sonochemistry, 2023)
The sonochemical generation of hydrogen (H2) was investigated using various water/alcohol solutions under argon (Ar) 100 % in a 300 kHz sonoreactor. Five types of alcohols–methanol, ethanol, isopropanol, n-propanol, and n-butanol–were used at various concentrations (0 – 100 % v/v). The H2 generation rate in water was 0.31 μmol/min in the absence of alcohols. The H2 generation rate increased, peaked, and then decreased as the alcohol concentration increased. The concentrations used for the peak H2 generation were 5 %, 1 %, 0.5 %, 0.5 %, and 0.1 % for methanol, ethanol, isopropanol, n-propanol, and n-butanol, respectively. The highest generation rate (5.46 μmol/min) was obtained for methanol 5 % among all conditions in this study, and no H2 was detected for 100 % alcohol concentrations. The reason for the enhancement of the sonochemical H2 generation by the addition of alcohols might be due to strong scavenging effect of alcohols for sonochemically generated oxidizing radicals and vigorous reactions of alcohol molecules and their derivatives with H radicals. No significant correlations were found between the H2 generation rates and physicochemical properties of the alcohols in any of the data in this study. As alcohol concentration increased, the calorimetric power decreased. This indicates that the calorimetric power does not represent the degree of sonochemical reactions in the water/alcohol mixtures. The effect of oxygen (O2) content in the dissolved gases on the generation of H2O2 (representing sonochemical oxidation activity) and H2 (representing sonochemical reduction activity) was investigated using Ar/O2 mixtures for water, methanol 5 % and n-propanol 0.5 %. In water, the highest H2O2 generation was obtained for Ar/O2 (50:50), which is similar to previous research results. However, the H2O2 generation increased as the O2 content increased. In addition, H2 generation decreased as the O2 content increased under all liquid conditions (water, methanol, and n-propanol).